Praktik Ekonomi Sirkular dan Manfaatnya bagi Kehidupan Sosial Ekonomi Petani: Studi Kasus pada Komditas Tebu, Jagung, dan Karet di Kabupaten Lampung Tengah - Seta, Amanda Putra; Endaryanto, Teguh; Firdasari, Firdasari; Sari, I Rani Melya (Hasanuddin University, 2025)
The sustainable development in Indonesia encourages the development of a green economy and a circular economy as an effort to integrate economic growth with environmental sustainability. This study aims to identify the pattern of circular economy practices along with their socio-economic benefits in Gunung Agung Village and Tanjung Anom Village, Central Lampung Regency, with a focus on sugarcane, corn, and rubber commodities. The data were collected through a purposive sampling method with 30 farmers as respondents. Furthermore, the data were analyzed descriptively using the 9R framework. The results show that agricultural wastes are beneficial as animal feed, organic fertilizers, fuels, and materials for making simple furniture. Socially, this practice has increased labour absorption and farmer knowledge, and economically has given additional income to farmers of about IDR 1.16 million (from sugarcane), IDR 1.52 million (corn), and IDR 1.59 million (rubber) per year. These findings indicate that the implementation of a circular economy has the potential to improve farmer welfare while supporting environmental sustainability.